#TITLE_ALTERNATIVE# - ANDRI KISNARTI (NIM 22405012), ENGKI
The three dimensional quasi model which have been developed by Uday Putrevu (1992-1993) from Center for Applied Coastal Research (CACR) tested by a sensitivity test to know what is the most significant wave parameter in alongshore current generation. Wave breaker angle increase causes alongshore current enlargement. This matter is caused by the enlargement of the x direction momentum flux, so the y direction momentum flux is enlarging too. Wave height increase, besides causing the enlargement of the alongshore current, it also causes the breaker wave length become longer. This matter occur because large wave height contains larger energy than small wave height This large energy caused the particle velocity at wave crest is bigger than the spreading wave velocity resulting the occurring of instability and breaking wave. Wave period increases causing alongshore current velocity increase although it’s percentage is just 0.93 %. In a quantitative way, sensitivity test indicates that the adding of wave breaker angle (4.33 %) gives bigger influence in producing alongshore current velocity compared to the adding of wave height (3.10 %) and wave period (0.93 %). Alongshore current can be seen in three dimensional form. In three dimensional pictures, alongshore current characteristic outside the surf zone indicates that surface velocity is bigger than the bottom velocity. This matter is caused by the wave energy has not reach the bottom of the sea. Alongshore current characteristic inside the surf zone indicates that the v component is more dominant than the u component. The shorecirc three dimensional quasi model is also compared with Longuet-Higgins analytic model. In the model test with Longuet-Higgins analytic solution shows good resemblance between numeric model and analytic computation results. In a quantitative way, both the Longuet-Higgins analytic and numeric results indicate the difference is less than 8.42 % (mean difference is 5.67 %). Validity was done to apply the shorecirc three dimensional quasi model in Dadap-Juntinyuat waters, Indramayu.was been done in the North of Indramayu city to be exact. The measurement of the current data (tracking) had been done in September 16th 2007. The results of the observations that had been done on the field and the simulation of alongshore current velocity model show that observation on the field is larger than the model simulation with the deviation standard is 0.051 meter/second.